2014
DOI: 10.3889/oamjms.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes and Patterns of Self-Medication with Antibiotics – A Cross-Sectional Study in Bulgaria

Abstract: BACKGROUND: Self-medication with antibiotics is a major concern worldwide because of the high risks of antimicrobial resistance which may result in complicated courses of treatment, increased risk of death and excess costs to the healthcare systems.AIM: The aim was to study the attitudes and self-medication patterns as related to the use of antibiotics among the general Bulgarian population and their determinants.MATERIALS AND METHODS: A questionnaire-based survey was performed among the patients in two random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…A total of 24 studies were identified and included in this scoping review study; the characteristics of the included studies are presented in Table 1. These studies were executed using different methodologies such as cross-sectional [12][13][14][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], quantitative, [40][41][42] and mixed-methods or observational designs [23]. The number of participants in these studies ranged from 100 to 2696 and publication dates ranged from 2009 to 2018.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 studies were identified and included in this scoping review study; the characteristics of the included studies are presented in Table 1. These studies were executed using different methodologies such as cross-sectional [12][13][14][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], quantitative, [40][41][42] and mixed-methods or observational designs [23]. The number of participants in these studies ranged from 100 to 2696 and publication dates ranged from 2009 to 2018.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The number of participants in these studies ranged from 100 to 2696 and publication dates ranged from 2009 to 2018. Data on attitude, prevalence, sociodemographic factors, predictors and causes of SMA were collected from self-completed questionnaires [13,14,[23][24][25][26][27][29][30][31]33,37], face-to-face interviews [32,36,38,40,41,43] and observer-rated compliance with recommendations [23]. Four of the studies were undertaken in Saudi Arabia [28][29][30]39], three in Pakistan [12,13,42], two studies in Jordan [40,41] and Turkey [38,41] and one each from Bangladesh, [24] Bulgaria [23], Beirut, [32] Cameroon [33] Columbia, [34] Greece, [25] Guatemala, [35] Haiti, [36] Indonesia [26] Cyprus, Egypt, Lebanon, Libya, Tunisia, [41] Nigeria, [14] Poland, [37] Portugal, [27] Romania, [43] and the United Arab Emirates …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of K. pneumoniae cases that were combined resistant to third generation cephalosporins, fluoroquinolones and aminoglycosides, in 2021, was 59.9% and 21.2% for Bulgaria and EU/EEA, respectively [ 26 ]. One of the main reasons for AMR is antibiotic consumption and Bulgaria is one of the European countries with a very high total consumption of antibiotics (24.4 DDD/1000 inhabitants/day for 2021) [ 27 , 28 , 29 ]. K. pneumoniae is also among the most common Gram-negative bacteria isolated to the NICU and one of the leading causes of morbidity and mortality [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%